Somatic cell count inversely related to potential profits in dairying - Dunham, James R. (Kansas Agricultural Experiment Station, 2011)
Somatic Cell Count (SCC) affects productivity of a dairy herd and, thus, potential profit. Almost all SCC problems can be solved by management. The DHIA SCC program is very useful for evaluating the situation in a dairy herd to solve such problems.
Keywords: Somatic cell count; Mastitis; Rolling herd average